Las nuevas fronteras de los derechos fundamentales en el ordenamiento italiano: crónica de un lento avance - Ortega Santiago, Carlos (Teoría y Realidad Constitucional, 2007)
Nowadays, the development of fundamental rights finds new spaces of expansion related to, among other subjects, the recognition of citizenship and the rights of foreigners, the satisfaction of new social demands that do not have express recognition in constitutional texts (such as the rights of unmarried couples —hetero or homosexual—), or the appropriate regulation of the new challenges that derive from the advances of science and the appropriate consideration of the varied rights and interests involved (for example, as it happens with test-tube fertilization and treatment of human embryos). Italian Law proves still to be resistant to adapt to those new challenges, without needing be to give up the ethical component that must preside over its legal discipline. In any case, that component must be looked up in the constitutional text and its update interpretation, but not in a morality that tries to establish itself as the collective morality of a society, even though it doesn’t become morality of State.